High Frequency of Multiple Antibiotic Resistance Index of Klebsiella pneumoniae Isolated from Different Hospitals in Baghdad, Iraq - Odaa, Farah Hadi; Al-Mathkhury, Harith Jabbar Fahad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The widespread use of antibiotics has contributed to a progressive rise of Klebsiella pneumoniae resistance to antibiotics, posing a challenge in the implementation of infection control. The current study aims to give an update on the antibiotic resistance status of local K.pneumoniae isolates. A total of one hundred and sixty specimens from different sources were collected. The VITEK 2 compact system was used to confirm the identification and test the antibiotic susceptibility. Multiple antibiotic resistance indices were estimated for each isolate. Out of the total samples, eighty (50%) K. pneumoniae isolates were identified by morphological and cultural characteristics and CHROM agar. Noticeably, the majority (28.75%) of the isolates in our investigation were obtained from cases of sputum. Moreover, piperacillin was the most resistant antibiotic (91.25%), whereas colistin (10%) was the least resistant antibiotic. 66 (82.5%) isolates were indicated as multidrug-resistant K. pneumoniae, and 13.6% of isolates were flagged as ESBL producers. What’s more, 71 (53.75%) isolates had a MAR value > 0.2. K. pneumoniae developed an increased resistance to antibiotics, mostly prescribed by local physicians.